Hubungan Tingkat Pengetahuan dengan Penyakit Gigi dan Mulut pada Santri di Pesantren Manarul Huda Bandung - Novianti Putri Hidayat; Meta Maulida; Lia Marlia (UNISBA Press, 2022)
Abstract. Dental and oral diseases can cause focal infections, meaning infections in body organs that are spread through the teeth and mouth. This will have an impact on life expectancy and quality of life. One of the many factors that can cause dental and oral disease is the level of knowledge about dental and oral health. If knowledge about oral and dental health is high, the incidence of oral and dental problems will be low. This study is intended to analyze the relationship between